2010
DOI: 10.1111/j.1558-5646.2010.01110.x
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-Dependent Fecundity Associates With Latitude in Caenorhabditis Briggsae

Abstract: Further, we determine experimentally that the mechanism underlying reduced fecundity at extreme temperatures differs for low versus high temperature extremes, but that the total number of sperm produced by the gonad is unaffected by rearing temperature. Low rearing temperatures result in facultatively reduced oocyte production by hermaphrodites, whereas extreme high temperatures experienced during development induce permanent defects in sperm fertility. Available and emerging genetic tools for this organism wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
145
3

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 72 publications
(166 citation statements)
references
References 71 publications
18
145
3
Order By: Relevance
“…Moreover, hermaphrodites of a given strain appear to produce roughly equal numbers of sperm regardless of the temperature regime (Fig.3). These results mimic a similar recent observation in C. briggsae, for which a role of defective sperm fertility was implicated as a main cause of temperature-dependent variation in fecundity, rather than sperm abundance per se (Prasad et al, 2011); experiments in C. elegans by Harvey and Viney also are consistent with this (Harvey and Viney, 2007). When C. elegans are grown in soil and compost microcosms, hermaphrodite fecundity also is not sperm limited (Goranson et al, 2005).…”
Section: Genetic and Environmental Influences On Fecundity And Sperm supporting
confidence: 78%
See 1 more Smart Citation
“…Moreover, hermaphrodites of a given strain appear to produce roughly equal numbers of sperm regardless of the temperature regime (Fig.3). These results mimic a similar recent observation in C. briggsae, for which a role of defective sperm fertility was implicated as a main cause of temperature-dependent variation in fecundity, rather than sperm abundance per se (Prasad et al, 2011); experiments in C. elegans by Harvey and Viney also are consistent with this (Harvey and Viney, 2007). When C. elegans are grown in soil and compost microcosms, hermaphrodite fecundity also is not sperm limited (Goranson et al, 2005).…”
Section: Genetic and Environmental Influences On Fecundity And Sperm supporting
confidence: 78%
“…However, some experimental evolution treatments did not conform to theoretical predictions, suggesting that existing theory on the evolution of sperm count in this system is incomplete and/or that alternative experimental approaches are required to fully test theoretical predictions. We also demonstrated that hermaphrodite fecundity is not sperm limited when individuals are reared at high and low temperatures, consistent with findings in C. briggsae (Prasad et al, 2011) and for other non-optimal growth conditions (Goranson et al, 2005). This suggests that environmental and ecological stress may generally lead to oocyte-limited reproduction in this organism, and conformity with Bateman's Principle (Bateman, 1948), rather than the sperm limitation observed under benign conditions.…”
Section: Experimental Evolution Of Sperm Numbersupporting
confidence: 75%
“…The fitness of different wild genetic backgrounds of C. briggsae is affected differentially by rearing temperature in accord with the strong phylogeographic patterning of this species in which genotype, phenotype and geographic distribution all are associated (Prasad et al, 2011). By contrast, C. elegans shows no comparable association between phenotypes and geographic origin, including differences in temperature-dependent fecundity (Hodgkin and Doniach, 1997;Rockman and Kruglyak, 2009;Anderson et al, 2011).…”
Section: Introductionmentioning
confidence: 87%
“…In particular, strains from the two most commonly isolated C. briggsae genetic groups suggest a latitudinal divide, and these two groups have been designated as 'temperate' and 'tropical' clades (Cutter et al, 2006). There is evidence of local adaptation for these groups, as strains from the 'tropical' clade have much higher fecundity at high temperatures (30°C) while 'temperate' clade strains have a higher fecundity at low temperatures (14°C) (Prasad et al, 2011). In both C. briggsae and C. elegans, sperm are sensitive to temperature, with sperm fertility negatively affected by high temperature during sperm development Prasad et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation